Investigating combined effect of WOM and eWOM: role of message valence. Issue 2 (27th January 2022) - R.V., ShabbirHusain; Varshney, Sanjeev
Abstract : Purpose: The purpose of this study was to investigate consumer preference formation in presence of reviews coming from traditional and electronic word of mouth (eWOM) under different conditions of review valence. Design/methodology/approach: Scenario-based experimental design was used for this study. A total of 172 respondents were randomly assigned across four experimental scenarios and a control group. Across-groups comparisons were conducted using post hoc Dunnett's test for checking the hypothesis. Findings: The study revealed that negativity bias impacted consumer judgement formation to such an extent that positive valence from higher credibility source (WOM) is over-powered by negative reviews from lesser trusted source (eWOM). Further, a negative valence review from higher credibility source (WOM) may not be countered even in presence of consensus of positive valence review coming from a higher number of positive eWOM. Originality/value: This study contributes to existing literature by examining consumer preference behaviour in presence of reviews coming from traditional and eWOM under different conditions of review valence. While earlier studies have examined individual role of WOM and eWOM under differing valence conditions, this paper extends literature by studying combined effect of WOM and eWOM under different review valence.